Comparative Preliminary Standardization of Siddha Medicated Oil: Thalangai Ennai, a Poly Herbal Formulation - Vinotha, S.; Ira, T.; Sri Ranjani, S. (International Journal of Scientific and Research Publications (IJSRP), 2016)
A poly herbal Siddha formulation, Thalangai ennai (T.E) was prepared as per the Siddha Literature and used as relieving rheumatic pains, impaired movement of limbs, and all kind of joint disorders, etc. The physicochemical standards available for the standardization of Siddha medicated oils are insufficient. This article reports on comparative preliminary standardization of T.E of Drug Unit (DUT) and Marketed formulation (MFT) have been standardized on the basis of organoleptic characters, physicochemical properties and analysis of Thin Layer Chromatography. Specific gravity and pH value for DUT was found to be 0.9185 and 4.61; in case of MFT these were found to be 0.9173 and 4.97 at room temperature respectively. The TLC finger prints of both the formulations were revealed fifteen spots in the pure dichloromethane solvent. The results obtained with these both the formulations were found to be comparable and variations were not remarkable. Though the analytical values can be used as reference standards for the quality assurance of T.E, these values mostly related to the purity of the sesame oil (which is used as a base), the qualitative and quantitative estimation of each single ingredient of T.E requires further research work in future.
Keywords: Thalangai ennai; Poly herbal formulation